Prevalence of chlamydial antibody in Malaysians. - Ngeow, Y.F.; Rachagan, S.P.; Ramachandran, S. (BMJ Publishing Group, 1990)
A single antigen indirect immunofluorescence test was used to screen for chlamydial antibody among Malaysian infants, children, sexually active adults and prostitutes. Of 794 serum samples tested, 361 (45.5%) were positive. Seropositivity increased with age and sexual activity and ranged from 10 to 16% among children under 10 years old to 94.4% among prostitutes. Pregnant women and female adolescents showed a higher antibody prevalence than nonpregnant and older women. Six (13%) infants under 6 months of age were positive for chlamydial IgM.